Simulasi Sistem Monitoring Kebun Pintar Berbasis IoT dengan Cisco Packet Tracer - Ni Kadek Dwi Marhaeni; Agus Muliantara (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
The agricultural sector faces the ongoing challenge of enhancing productivity while ensuring sustainability. Inspired by previous research on automatic irrigation sensors, the concept of a smart garden has emerged as a promising solution. This study extends prior work by developing and implementing four distinct sensors: temperature, automatic watering, air humidity, and motion sensors. Leveraging machine-to-machine communication, these sensors integrate into an environmental monitoring system to optimize resource utilization and maintain ideal plant conditions. By utilizing Cisco Packet Tracer software, this research simulates a comprehensive smart garden system, offering insights into monitoring garden environments and automating agricultural processes. With a focus on data-driven decision-making, this study contributes to a smarter, more sustainable agricultural vision.